FeCo/FeCoNi/N-doped carbon nanotubes grafted polyhedron-derived hybrid fibers as bifunctional oxygen electrocatalysts for durable rechargeable zinc–air battery - Wang, Zhe (2021)
The rational design and exploration of highly efficient, low-cost, and robust electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is critical for development of rechargeable metal-air batteries. Herein, we report a novel approach for the synthesis of bifunctional electrocatalysts, where Fe0.5Co0.5 and Fe0.5Co0.4Ni0.1 alloys are encapsulated in the nitrogen-doped carbon nanotubes-grafted porous polyhedron-derived hybrid fibers (FeCo/FeCoNi@NCNTs-HF). Benefiting from its hierarchically porous structure and strong synergetic coupling among FeCo, FeCoNi alloys, and N-doped carbon species. The obtained electrocatalyst exhibits a positive half-wave potential of 0.850 V for ORR and a low potential of 1.608 V to achieve a current density of 10 mA cm−2 for OER, as well as superior stability in alkaline media. As a demonstration, FeCo/FeCoNi@NCNTs-HF is employed as the electrocatalysts in the air cathode of a Zn-air battery, which shows superior discharge and charge performance, large power density, high specific capacity, and outstanding cycling stability of 240 h (360 cycles). More impressively, excellent cyclabilitiy with a lifetime of 670 h (1005 cycles) is also achieved by the Zn-air battery with FeCo/FeCoNi@NCNTs-HF as the self-supported air electrode. This work will open a novel avenue to develop advanced bifunctional electrocatalysts for the next generation of metal-air batteries.